The Astragalus minimus(Leguminosae,Galegeae) Complex and One Species for Chile and Argentina - Gomez, Edith Vilma (2010)
Astragalus minimus Vogel (Leguminosae) is endemic to the Andean region of South America, in Peru, Bolivia, Chile, and northwestern Argentina. This taxon belongs to a pulvinate species complex in the genus Astragalus L. (Leguminosae, Galegeae) from high mountain puna vegetation, between 4000 and 4500 m in the Neotropics. The A. minimus complex is newly delimited, in particular with information for the fruit, which was not described in Vogel's 1843 protologue. This new information allows the identification of A. tacorensis Gómez-Sosa as a species new to science; both taxa are morphologically described and illustrated.